P371 The addition of intravenous, high dose, bolus of methyl-prednisolone increases the early clinical response to oral corticosteroids in moderately active ulcerative colitis. Preliminary results of a prospective, controlled, multicentre, randomised, open-label study. (21st January 2022) - Domènech Moral PhD, E; Llaó, J; Mañosa, M; Martín-Arranz, E; Zabana, Y; Navarro-Llavat, M; Garcia-Planella, E; Busquets, D; Pineda, J R; Monfort, D; Gutiérrez, A; García-Alonso, F J; et al.
Abstract: Background: Oral corticosteroids remain the treatment of choice for moderately active flares of ulcerative colitis (UC). In early controlled studies, oral corticosteroids achieved clinical remission rates of, 30–60% at, 30 days. Some small prospective studies observed that the administration of high-dose intravenous bolus of methyl-prednisolone accelerated their therapeutic action and increased the rate of clinical response. We aimed to evaluate if the outpatient administration of intravenous, high-dose, methyl-prednisolone bolus increases the efficacy of a conventional course of oral prednisone in moderately active UC. Methods: Prospective, multicentre, controlled, randomized, open-label study comparing the therapeutic efficacy of a standard oral prednisone schedule with the same schedule preceded by a three-day regimen of high-dose intravenous bolus of methyl-prednisolone. Inclusion criteria were: Moderately active, left-sided/extensive UC (total Mayo score, 6–10), with no prior exposure to immunosuppressants or biologics, and no corticosteroid treatment in the last, 6 months. Patients were randomized to oral prednisone, 60mg/day (ORAL group) or the same schedule preceded by intravenous bolus of, 500mg of methyl-prednisolone for three consecutive days (BOLUS group), stratified by the baseline use of oral, 5ASA and UC onset. Early clinical response was defined as the reduction of the baseline partial Mayo Score (pMS) by at least three points with at least a decrease by, 1 point in rectal bleeding and with an absolute value of, 0 or, 1, seven days after starting treatment (EUDRA CT:, 2016-001170-15)(Clinicaltrials.gov: NCT02921555) Results: In all, 71 patients (38 ORAL, 33 BOLUS) were included. At baseline, the median pMS was, 6 (IQR, 5–7). In, 21% of the patients, the index flare was the onset of UC and, 68% had never received systemic corticosteroids for UC. There were no differences in baseline clinical and demographic features between the two study groups. At day, 7, the proportion of patients fulfilling early clinical response criteria was similar in both groups (BOLUS, 63% vs. ORAL, 58%; p = 0.6), but a significantly greater reduction in pMS at day, 3 (-3.4. vs -1.7; p <0.0001) and a significantly higher proportion of patients in clinical remission (pMS <2) at day, 7 (57% vs, 29%; p = 0.017) were observed in the BOLUS group. Conclusion: The addition of three high-dose intravenous bolus of methyl-prednisolone to a standard schedule of oral corticosteroids achieves a faster and more intense response in the short-term in moderately active flares of UC, but it does not increase the clinical response rate at seven days. The impact of these effects on the medium-term outcomes is still to be assessed.